PERKEMBANGAN MANUSIA DALAM PANDANGAN PSIKOLOGI DAN AL-QUR’AN - Khotima, Husnul; Oktariani, Humairo; Aisyah, Neng; Harto, Kasinyo; Amilda, Amilda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The human creation of god has a perfect form in relation to his other creatures. Human development is essentially a fixed pattern with which each individual in general is a development that involves growth from the stage of conception down to the length of one's life span. The Koran contains several scriptures that show human development. Therefore the "development" of the Koran will be tried to compare with the discipline of psychology, the purpose of this study is to know the phases of human development in the psychology and the qur 'an. The study is a study of literature, where resources are derived from various literature relating to human development. The result of this study is that human development is characterized by physical changes and human attitudes, which are associated with several aspects of human development, and in qur 'an studies, suggests that it influences human development in the environment.